Incidence of Kinsbourne syndrome in patients diagnosed with neuroblastic tumors: a single-center experience and review of literature - Katarzyna Kuchalska; Monika Barełkowska; Anna Gotz-Więckowska; Katarzyna Derwich (Hygeia Press di Corridori Marinella, 2022)
Kinsbourne syndrome or opsoclonus-myoclonus syndrome (OMS), also called dancing feet syndrome, manifests in opsoclonus, myoclonus, and ataxia. It occurs more frequently in pediatric patients, and around 50% of cases are caused by neuroblastoma (NBL). This investigation aimed to determine the incidence of OMS in children diagnosed with neuroblastic tumors. Data collected from 2004 to 2019 at the Department of Pediatric Oncology, Hematology, and Transplantology of Poznań University of Medical Sciences (Poznań, Poland) were analyzed. The research group included 119 patients under 18 years of age. There were only 3 cases (2.52%) of OMS in the research group, all younger than 3 years. The tumor was localized in the adrenal gland in 1 patient and paravertebrally in the other 2. The presented symptoms included nystagmus, balance disturbances, and tremors. All cases of OMS in children require imaging to determine whether it is caused by NBL. However, among patients with NBL, OMS is a rare manifestation.